Vulvar malignant melanoma: a rare tumor with worse prognosis - Singh, Swati; Singh, Prem; Kaur, Navdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Malignant melanoma, which has a highly malignant potential, is a tumor of the skin and mucosal membranes. Malignant melanomas of the female genital tract, including the vulva and vagina, are rare. Their overall prognosis is worse. A 75 year old woman presented with complaint of growth in vulvar region since 4 months. There was history of itching in vulvar region over growth. Surgery is still the best available treatment for the control and potential cure of malignant melanomas.